HEPATOCELLULAR CARCINOMA: CORRELATION OF ALPHA-FETOPROTEIN WITH TUMOUR CHARACTERISTICS - Rafi Ud Din; Adnan Qadir; Rao Saad Ali; Amjad Salamat (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine the correlation of alpha-fetoprotein (AFP) levels with tumour characteristics in hepatocellular carcinoma (HCC).